Managing biology learning for sustainability: Prospective teachers’ perceptions and readiness - Ikmanisa Khairati; Lufri Lufri; Festiyed Festiyed; Mawardi Mawardi; Usmeldi Usmeldi (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
Education for Sustainable Development (ESD) as a means to support the achievement of sustainability goals must become the core of the learning process. This is inherently connected to the crucial role of teachers in incorporating the concept of sustainability within the learning process. This research aims to gain insights into the perceptions and competencies of prospective teachers, reflecting their readiness to implement ESD into biology teaching. Referring to the Evidence for Policy and Practice Information and Co-ordinating Center (EPPI-Center) framework for systematic literature review in educational research, this study examines empirical studies from the Scopus electronic database published between 2015 and 2024, focusing on studies in the field of biology education and ESD. The review followed three main stages: determination of inclusion and exclusion criteria, keyword selection, and systematic categorization. Data analysis was conducted using a content analysis approach. The findings were categorized into four main themes: perceptions and self-efficacy; prospective teachers’ competencies; ESD learning strategies for prospective teachers; and psychological and social factors. The results of this review provide evidence for identifying areas for future exploration aimed at improving the competencies of prospective teachers in implementing ESD.Abstrak. Education for Sustainable Development (ESD) sebagai upaya untuk mendukung pencapaian tujuan keberlanjutan, harus menjadi inti dari proses pembelajaran. Hal ini tentunya tidak terlepas dari peran penting guru dalam mengintegrasikan konsep keberlanjutan ke dalam proses pembelajaran. Penelitian ini bertujuan untuk mendapatkan wawasan tentang persepsi dan kompetensi calon guru yang mencerminkan kesiapan mereka dalam mengimplementasikan ESD ke dalam pembelajaran biologi. Mengacu pada kerangka kerja Evidence for Policy and Practice Information and Co-ordinating Center (EPPI-Center) untuk tinjauan literatur sistematis dalam penelitian pendidikan, penelitian ini mengkaji studi empiris dari database elektronik Scopus yang diterbitkan antara tahun 2015 hingga 2024, dengan fokus pada studi di bidang pendidikan biologi dan ESD. Tinjauan ini mengikuti tiga tahap utama: penentuan kriteria inklusi dan eksklusi, pemilihan kata kunci, dan kategorisasi sistematis. Analisis data dilakukan dengan menggunakan pendekatan analisis isi. Temuan dikategorikan ke dalam empat tema utama: persepsi dan kepercayaan diri; kompetensi calon guru; strategi pembelajaran ESD untuk calon guru; serta faktor psikologis dan sosial. Hasil kajian ini memberikan bukti untuk mengidentifikasi bidang-bidang yang perlu dieksplorasi di masa depan yang bertujuan untuk meningkatkan kompetensi calon guru dalam mengimplementasikan ESD.